27. Metallic hip implants: Are avoidance sectors necessary for pelvic VMAT treatments?. (December 2017) - Koutsouvelis, N.; Dipasquale, G.; Rouzaud, M.; Miralbell, R.; Zilli, T.
Abstract : Introduction: Avoidance of metallic hip implants (MHI), especially when bilateral, deteriorates the quality of RT treatments, with a significant increase in the dose delivered to the healthy tissues. The aim of this study was to investigate the dosimetric impact of MHI with or without use of avoidance sectors (AS) in classical VMAT planning for pelvic tumors and to assess the in vivo dose calculation errors in the presence of MHI. Methods: In this study we evaluated: (1) The dosimetric impact of AS as assessed on CT planning datasets of four male patients with bilateral MHI (each patient planned for a whole pelvis VMAT to 64 Gy for bladder cancer treatment and for a prostate only VMAT treatment to 78 Gy). No-AS plans: 2 coplanar arcs/ optimization realized as in a classical pelvic VMAT treatment without MHI. AS plans: AS were chosen in a way that no part of the beam passed through the MHI to hit the target. (2) The dose calculation error of a static open beam output through a MHI, using a titan and a ceramic hip prosthesis model in a homemade phantom, 4 different detectors, and 3 different beam energies. (3) The dose calculation error in the PTV during a non-AS 360° VMAT treatment, given the static beam error introduced by the MHI. (4) The dosimetric influence of MHI shifts generated by patient's repositioning tilts for IGRT purposes. Results: (1) Compared to VMAT plans generated without AS, for all treatment plans, the use of AS resulted in a median increase of the rectal V50Gy and V60Gy by 424% and 339% respectively, and deteriorated the conformity. For prostate treatment plans, a median increase of 56%, 48% and 19% was observed for bladder V60Gy, V65Gy, and V75Gy respectively, when using AS. (2) For distances between 0.5 cm and 6 cm after the MHI, the deviations of measurements from calculations were not significant. On the surface of the MHI, significant deviations −12% and −14% were observed with EBT3 films, for the CHP and the titanium material respectively (only X6 beam tested). (3) For a given static open beam error (point2), introduced by the MHI in the PTVs, the respective 360° VMAT treatments showed a decrease of this error by a median factor of 4 (Annexe). (4) Patient's tilt must not lead in a MHI anterior-posterior shift of more than 4 mm, in order to have a maximum error of 1% at the PTV borders. Conclusions: In patients with bilateral MHI treated with pelvic 360° VMAT, creation of AS for treatment planning is not mandatory, especially when the distance between the prosthetic material and the target volume is more than 5 mm. Planning improvement in terms of simplicity, conformality and organ sparing is expected by irradiating through MHI when using VMAT techniques.